Advances in artificial intelligence models and algorithms in the field of optometry - Wang, Suyu; Ji, Yuke; Bai, Wen; Ji, Yun; Li, Jiajun; Yao, Yujia; Zhang, Ziran; Jiang, Qin; Li, Keran (Frontiers in Cell and Developmental Biology, 2023)
The rapid development of computer science over the past few decades has led to unprecedented progress in the field of artificial intelligence (AI). Its wide application in ophthalmology, especially image processing and data analysis, is particularly extensive and its performance excellent. In recent years, AI has been increasingly applied in optometry with remarkable results. This review is a summary of the application progress of different AI models and algorithms used in optometry (for problems such as myopia, strabismus, amblyopia, keratoconus, and intraocular lens) and includes a discussion of the limitations and challenges associated with its application in this field.